The Effect of Tax Justice and Tax Discrimination on The Intention to Commit Tax Evasion by Prospective Taxpayers - Wardani, Dewi Kusuma; Kusumastuti, Aprilia (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to examine whether tax justice, tax discrimination have an influence on the intention to commit tax evasion for prospective taxpayers. The sample population of this study were all students in the Special Region of Yogyakarta (DIY). In this study the authors used the snowball sampling method. For data collection, the authors used a questionnaire distributed in the form of a google form. The distribution of the questionnaire obtained 123 respondents. The results of the study stated that tax justice have a negative effect on the intention to commit tax evasion. While discrimination has no effect on the intention to commit tax evasion.